A Critical Reading, Appreciation, and Assessment of Responses to on Being Human - Díaz, Miguel (Philosophy & theology, 2004)
This essay represents a critical reading, appreciation and assessment of responses written by Susan Abraham, Conrad T. Gromada, and Michael Barnes to my book On Being Human: U.S Hispanic and Rahnerian Perspectives (Orbis Books, 2001). The essay addresses the following three themes: 1) Rahner’s Ignatian heritage and its relation to the U.S. Hispanic appropriation of the preferential option for the poor and marginalized, 2) Rahner’s understanding of one mediator and many human mediations, and 3) Rahner’s transcendental theological approach in relation to the experience of contemporary manifestations of atheism in the U.S. These themes highlight aspects of my book that Abraham, Gromada, and Barnes found fertile ground for engaging in theological conversation. First, with respect to Rahner’s Ignatian spirituality, I argue that the Ignatian understanding of indiferencia can be correlated with the preferential option for the poor and marginalized. Second, with respect to Rahner’s understanding of one mediator and many mediations, I explore other ways in which my book could contextualize Rahner’s approach. Finally, I underscore the historical moment in Rahner’s transcendental theological approach (the mystery of God encountered in, with, and under historical realities) and point to a contemporary implication of this understanding (e.g., practical atheism).